MENUMBUHKAN KEMBANGKAN BUDAYA MENULIS KARYA ILMIAH DI ERA 5.0 PADA PESERTA DIDIK MA/SMA DAN MAHASISWA FAI UNDARIS UNGARAN KABUPATEN SEMARANG (PENULISAN ESAI SEJARAH ISLAM) - Priarni, Rina; Zamani, Badrus (Tahta Media Grup, 2023)
Writing culture is a habit of conveying messages, expressing opinions and creating documentation. By writing we will have the habit of conveying systematic opinions. Writing also stimulates creativity. By writing, fresh ideas will emerge. Writing is a language skill that is very expressive and productive. It is said to be expressive because writing is the result of thoughts and feelings that can be expressed through the activity of moving fine motor skills through the strokes of our hands. Furthermore, it is said to be productive, because it is the process of producing units of language in the form of real works, until they are born in written form. Recently, the problem of the lack of student writing productivity has begun to be discussed.Both in print and electronic media. Various discussion forums were opened, such as holding seminars on writing and soft skills training on writing. This is done to